The economics of money, banking, and financial markets - Mishkin, Frederic S. (Pearson/Addison Wesley, 2007)
"'Economics of Money, Banking, and Financial Markets 'heralded a dramatic shift in the teaching of the money and banking course in its first edition, and today it is still setting the standard. By applying an analytical framework to the patient, stepped-out development of models, Frederic Mishkin draws students into a deeper understanding of modern monetary theory, banking, and policy. His landmark combination of common sense applications with current, real-world events provides authoritative, comprehensive coverage in an informal tone students appreciate. Mishkin's previous post as Executive Vice President and Director of Research at the Federal Reserve Bank of New York lends an insiders-view that helps to demystify this key institution for students." -- Publisher's website